1979
DOI: 10.1002/ijc.2910240302
|View full text |Cite
|
Sign up to set email alerts
|

“NK‐like” cytotoxicity of human lymphocytes cultured in media containing fetal bovine serum

Abstract: Human peripheral blood lymphocytes (PBL) were found to be highly cytotoxic to a human malignant melanoma target cell line after the PBL were cultured in medium supplemented with 20% fetal bovine serum (FBS). The effector cells had surface markers similar to those of non-cultured NK effectors against melanoma targets. Both NK (without culture) and the culture-induced cytotoxic effectors had Fc gamma receptors, lacked Fc mu receptors and were either heterogeneous for E receptors or had low-affinity E receptors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1981
1981
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…A variety of other phenomena producing human cells lytic for tumor cells have been described, including natural killer [1,2,10,25], mixed lymphocyte-tumor reactions, some with classic CTL-type cytotoxicity [9,21,30,45,47], anomalous cytotoxicity [32], lectin incubation [23], lymphokine activation [11], activated cell killing [22], activation by BCG, tuberculin or staphylococcus filtrates [33,38], N cell activation [17], activation by xenogeneic serum [50], and activated macrophage killing [37]. The lysis demonstrated in these reports was predominantly assayed against tissue culture tumor with fresh autologous tumor target cells tested only rarely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of other phenomena producing human cells lytic for tumor cells have been described, including natural killer [1,2,10,25], mixed lymphocyte-tumor reactions, some with classic CTL-type cytotoxicity [9,21,30,45,47], anomalous cytotoxicity [32], lectin incubation [23], lymphokine activation [11], activated cell killing [22], activation by BCG, tuberculin or staphylococcus filtrates [33,38], N cell activation [17], activation by xenogeneic serum [50], and activated macrophage killing [37]. The lysis demonstrated in these reports was predominantly assayed against tissue culture tumor with fresh autologous tumor target cells tested only rarely.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration of cytotoxic cells that lyse autologous tumor in humans using specific sensitization to putative tumor antigens either in vivo or in vitro has been difficult and little success has been achieved [10,21,34,45]. Recently however, Zafling et al [48] demonstrated that cells sensitized in vitro to a pool of allogeneic lymphocytes developed the ability to lyse autologous human leukemia cells.…”
Section: Introductionmentioning
confidence: 98%
“…The LAK killing system is probably the final common pathway that explains many of the nonclassical cellular cytotoxicities reported previously, though fresh tumor cells were usually not used as target cells in such studies. These reports include activated cell ~killing (16), fetal calf serum-induced killing (19)(20)(21), and lectin-stimulated killing (18). Previous reports from our laboratory support the hypothesis that LAK may be generated from primary stimuli other than IL-2, but in which IL-2 is also generated, such as during allosensitization (23) or during lectin activation with T ceil mitogens (24), because in our reports, effectors were generated that did kill fresh autologous solid tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Such reports include anomolous cytotoxicities, distinct from CTL during alloactivation (13)(14)(15)(16)(17), lectinactivated killing, distinct from lectin-dependent killing (18), fetal calf serum cultureinduced killers (16,(19)(20)(21), and mixed-lymphocyte tumor interaction (MLTI)-induced killers, found only when proliferation was stimulated (8)(9)(10)(11)22). Though fresh tumor targets were rarely used in those studies, our previous reports of lysis of autologous fresh solid tumor cells after allosensitization (23) or lectin activation (24), and those of others after MLTI (8)(9)(10)(11), support this hypothesis and suggest that lymphokine activated killers (LAK) represent a unique and fundamental cytotoxic effector system that may play a role in immune surveillance against NK resistant solid tumor cells, and may have a possible role in the adoptive immunotherapy of tumors.…”
mentioning
confidence: 99%
“…Biddison et al [4] and Pope et al [5] described nonspecific cytotoxic activity stimulated in vitro by tumor cells. Activated killer cells also have been generated in vitro in the presence of fetal calf scrum or other xenogenic sera [6,7], Bach et al [8] have observed this phenomenon when cytotoxic responses to a single alloantigen or to a pool of alloantigens of a species have been assessed. Also incubation of normal cells with T-cell growth factor [interleukin-2 (IL-2)] will bring about this tu mor lysis [9], Likewise, incubation of lymphocytes with concanavalin A or phytohemagglutinin will generate cells capable of tumor lysis, but incapable of lysing normal tissues [10].…”
Section: Introductionmentioning
confidence: 99%